Determination of chromium, cobalt and nickel in the blood of the adult population living in Belgrade - Repić, Aleksandra; Lukić, Vera; Ždrale, Branislava; Javorac, Dragana; Bulat, Petar; Bulat, Zorica (Archives of Pharmacy, 2022)
The microelements chromium, cobalt and nickel are necessary for the proper functioning of the organism. At higher concentrations, they can cause toxic effects (organ disfunction, genetic damage). They are widespread in the enviroment. They reach our body through food, water, air and/or skin. The aim of this study was to determine the reference values of chromium, cobalt and nickel in the blood of adult residents of Belgrade and determine the degree of influence of individual, socioeconomic factors and lifestyle habits on blood levels of these metals. The study population consisted of adults, healthy population, 18 to 65 years of age, who were voluntary blood donors. The study included 715 men (72.7%) and 269 women (27.3%). Blood collected in vacutainers with heparin, was used for analysis. 984 samples were analysed. The metals were determined using inductively coupled plasma mass spectrometry (7700x, Agilent, USA), with octopol reactive system and micro-flow nebulizer. The average age of participants was 37.2± 10.8. The reference values of the analysed metals, shown as the 95 percentile, were 0.95mg/L, 0.62mg/L and 1.46mg/L for chromium, cobalt and nickel, respectively, and were in good correlation with the values obtained in biomonitoring studies conducted in Europe. This study showed that population of Serbian origin had significantly lower blood concentrations of chromium, that cobalt blood levels in women were significantly higher and cobalt and nickel levels increased with age in both sexes. Education and economic status, cigarette smoking and sports did not significantly affect the levels of these metals in the blood.